2009
DOI: 10.1503/cmaj.081364
|View full text |Cite
|
Sign up to set email alerts
|

Generalized tonic-clonic seizure after a taser shot to the head

Abstract: T he taser stun gun, manufactured by Taser International in Scottsdale, Arizona, is a weapon used increasingly among law enforcement personnel to temporarily incapacitate detainees. Questions have arisen in both the scientific literature and the lay press about the device's safety. [1][2][3] In this article, we report the occurrence of a generalized tonic-clonic seizure in a person who received a taser shot to the head. Case reportThe patient was a previously well police officer in his 30s who took part in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 7 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…No follow up CK is mentioned in the case report. In this case, the officer too had other risk factors for an elevated CK: involvement in a foot chase, a 1-min seizure, and post-ictal combativeness [13]. Rhabdomolysis has been reported in other arrest-related cases in which a TASER was not used.…”
Section: Discussionmentioning
confidence: 78%
“…No follow up CK is mentioned in the case report. In this case, the officer too had other risk factors for an elevated CK: involvement in a foot chase, a 1-min seizure, and post-ictal combativeness [13]. Rhabdomolysis has been reported in other arrest-related cases in which a TASER was not used.…”
Section: Discussionmentioning
confidence: 78%
“…Lim and Seet 85 were surprised, considering the vulnerability of nervous tissue to thermal injury, that neurological effects were not reported more frequently after ECD exposures. Although Bui et al 86 recently reported neurological sequelae of ECD applications, these were not thermal in nature. In a population-based study of 426 ECD activations by law-enforcement personnel, 87 only one death was subsequently attributed to hyperthermia.…”
Section: Body Temperaturementioning
confidence: 98%
“…Therefore, it might probably be assumed that it was the Taser current passing from the probe through the occipital area of the brain that triggered the seizure [7]. Indeed, it seems less likely that the seizure resulted from a direct impact of the head on the ground because the period of unconsciousness was too prolonged.…”
Section: Discussionmentioning
confidence: 99%